PENERAPAN NILAI-NILAI KARAKTER PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to determine how the application of character values in social studies learning in SMP Negeri 18 Makassar, whatever, which is a factor supporting and inhibiting factors in the application of character values in social studies learning in SMP Negeri 18 Makassar, and how the implications of the application of values character values in social studies learning in SMP 18 Makassar.This type of research used in this research is descriptive qualitative, ie a process of collecting data systematically and intensively to acquire knowledge and information. So in this study, researchers observe and interact with the principal, waka curriculum, social studies teacher and the students of SMP Negeri 18 Makassar with interviews and search for data by reviewing documentation.Based on the research results to obtain the result that the application of character values in social studies learning in SMP 18 Makassar is through policies of the principal to implement the values of the characters in each learning especially those on learning social studies, social studies teacher in the business of applying the values of character which includes a three -stage process: first the planning, implementation and evaluation. Supporting factor in the application of the values of the characters in SMP Negeri 18 Makassar with the availability of school facilities that support the implementation of the values of character, while the inhibiting factor has not been found to be significant. The implications of the development or application of the values of characters that can be observed through several advances such as improved learning environment, improvement of the quality of the school environment, improvement of the quality of social relationships in school, improved student academic achievement and creativity in extracurricular activities